Pathways to a rising caesarean section rate: a population-based cohort study. Issue 5 (4th September 2012) - Roberts, Christine L; Algert, Charles S; Ford, Jane B; Todd, Angela L; Morris, Jonathan M
Abstract : Objectives: To determine whether the obstetric pathways leading to caesarean section changed from one decade to another. We also aimed to explore how much of the increase in caesarean rate could be attributed to maternal and pregnancy factors including a shift towards delivery in private hospitals. Design: Population-based record linkage cohort study. Setting: New South Wales, Australia. Participants: For annual rates, all women giving birth in NSW during 1994 to 2009 were included. To examine changes in obstetric pathways two cohorts were compared: all women with a first-birth during either 1994–1997 (82 988 women) or 2001–2004 (85 859 women) and who had a second (sequential) birth within 5 years of their first-birth. Primary outcome measures: Caesarean section rates, by parity and onset of labour. Results: For first-births, prelabour and intrapartum caesarean rates increased from 1994 to 2009, with intrapartum rates rising from 6.5% to 11.7%. This fed into repeat caesarean rates; from 2003, over 18% of all multiparous births were prelabour repeat caesareans. In the 1994–1997 cohort, 17.7% of women had a caesarean delivery for their first-birth. For their second birth, the vaginal birth after caesarean (VBAC) rate was 28%. In the 2001–2004 cohort, 26.1% of women had a caesarean delivery for their first-birth and the VBAC rate was 16%. Among women with a first-birth, maternal and pregnancy factors and increasing deliveries in private hospitals, only explained 24% of the rise in caesarean rates from 1994 to 2009. Conclusions: Rising first-birth caesarean rates drove the overall increase. Maternal factors and changes in public/private care could explain only a quarter of the increase. Changes in the perceived risks of vaginal birth versus caesarean delivery may be influencing the pregnancy management decisions of clinicians and/or mothers.